Enhancing photothermal cancer therapy by clustering gold nanoparticles into spherical polymeric nanoconstructs. (January 2016) - Iodice, Carmen; Cervadoro, Antonio; Palange, AnnaLisa; Key, Jaehong; Aryal, Santosh; Ramirez, Maricela R.; Mattu, Clara; Ciardelli, Gianluca; O'Neill, Brian E.; Decuzzi, Paolo
Abstract: Gold nanoparticles (AuNPs) have been proposed as agents for enhancing photothermal therapy in cancer and cardiovascular diseases. Different geometrical configurations have been used, ranging from spheres to rods and more complex star shapes, to modulate optical and ablating properties. In this work, multiple, ultra-small 6 nm AuNPs are encapsulated into larger spherical polymeric nanoconstructs (SPNs), made out of a poly(lactic acid-co-glycol acid) (PLGA) core stabilized by a superficial lipid-PEG monolayer. The optical and photothermal properties of the resulting nanoconstructs (Au-SPNs) are modulated by varying the initial loading input of AuNPs, ranging between 25 and 150 μgAu . Au-SPNs exhibit a hydrodynamic diameter varying from ~100 to 180 nm, growing with the gold content, and manifest up to 2-fold increase in thermal energy production per unit mass of gold for an initial input of 100 μgAu . Au-SPNs are stable under physiological conditions up to 7 days and have direct cytotoxic effect on tumor cells. The superior photothermal performance of Au-SPNs is assessed in vitro on monolayers of breast cancer cells (SUM-159) and tumor spheroids of glioblastoma multiforme cells (U87-MG). The encapsulation of small AuNPs into larger spherical nanoconstructs enhances photothermal ablation and could favor tumor accumulation. Highlights: Photothermal therapy represents a promising strategy for the localized ablation of malignant tissues that cannot be removed via surgical resection. The efficacy of ablation therapies can be improved by combining the energy source with agents that could both specifically accumulate within the diseased tissue and enhance the energy conversion into heat. Gold nanoparticles (AuNPs) have been shown to be an ideal agent for enhancing laser-based ablation therapies mostly because of their tunable optical properties and surface plasmon resonance (SPR) effect. In order to improve the biodistribution performance of AuNPs and their ablation properties, in this work multiple 6 nm spherical gold nanoparticles have been encapsulated into a larger polymeric nanoconstruct. The superior optical and ablation properties of these polymeric nanoconstructs are demonstrated.